2016
DOI: 10.1016/j.pec.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Nursing staff and euthanasia in the Netherlands. A nation-wide survey on attitudes and involvement in decision making and the performance of euthanasia

Abstract: Nursing staff should be informed of relevant existing legislation and professional guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 19 publications
1
56
1
7
Order By: Relevance
“…22 Similarly, Francke et al found that 46% of 587 Dutch nurses stated a patient was more likely to address a request for euthanasia to a nurse than to a physician. 17 However, nurses alongside physicians were seen as important actors throughout the entire care process surrounding MAiD, from initial consultation all the way through to the administration of the assisted death. 13,16,17,21,23,24,27 Mental health providers were likely to encounter patients exploring MAiD among those with depression, anxiety, and other mental disorders, which may or may not be tied to a terminal diagnosis.…”
Section: Roles Of Health Care Professionalsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Similarly, Francke et al found that 46% of 587 Dutch nurses stated a patient was more likely to address a request for euthanasia to a nurse than to a physician. 17 However, nurses alongside physicians were seen as important actors throughout the entire care process surrounding MAiD, from initial consultation all the way through to the administration of the assisted death. 13,16,17,21,23,24,27 Mental health providers were likely to encounter patients exploring MAiD among those with depression, anxiety, and other mental disorders, which may or may not be tied to a terminal diagnosis.…”
Section: Roles Of Health Care Professionalsmentioning
confidence: 99%
“…17 However, nurses alongside physicians were seen as important actors throughout the entire care process surrounding MAiD, from initial consultation all the way through to the administration of the assisted death. 13,16,17,21,23,24,27 Mental health providers were likely to encounter patients exploring MAiD among those with depression, anxiety, and other mental disorders, which may or may not be tied to a terminal diagnosis. 29e31 In some cases, it was recommended that patients requesting MAiD be referred to a mental health provider to receive additional information and supports to help navigate end-of-life decision making.…”
Section: Roles Of Health Care Professionalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[21,22] Alternatively, future research may set out to evaluate physician's knowledge and perceptions related to MAID in order to highlight any differences. As a healthcare provider's role in MAID varies based on occupation, it would be valuable to compare the results of these two populations to determine if any similarities or differences exist so educational resources can be tailored to specific groups of healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…Allerdings sieht auch etwa ein Drittel der Befragten die ärztliche Gewissenfreiheit durch diese Regelung als eingeschränkt an. Diese Frage wurde auch den Pflegenden gestellt, da sie eng in die Therapie am Lebensende involviert sind, obwohl sie zu entsprechenden Handlungen nicht legitimiert sind [32]. Die Therapiefreiheit war nur von einer Minderheit als eingeschränkt angesehen worden.…”
Section: Diskussionunclassified